INNOVATION TO IMPROVE FINANCIAL ACCESS FOR THE POOR THROUGH GOVERNMENT ASSISTANCE PROGRAMMES IN FOSTERING FINANCIAL INCLUSION: PAYMENT SYSTEMS, BRANCHLESS BANKING AGENTS, AND BIOMETRIC AUTHENTICATION - Palaon, Hilman
Digitizing government assistance programmes for the poor in the form of social assistance and subsidy has been proven to increase financial inclusion. Previous studies argue that financial inclusion has an important role in increasing economic growth and reducing poverty. Moreover, from the government perspective, this approach also has the potential to save the state budget, to improve productivity and accountability, and to expand digital payment ecosystems. This dissertation discusses how the Indonesian Government took advantage of innovation in conducting non-cash social assistance reform that led to an increase in the financial inclusion index. This dissertation study consists of three research projects: the payment system selection, branchless banking agents business sustainability, and biometric authentication for payments. Three action research cycles were conducted to analyze these three research focuses. The government requires evidence to make new policy. The first action research cycle discusses the selection of a payment system for distributing non-cash social assistance programme to the poor. In 2016, a pilot project involving 4,295 participants was conducted to evaluate the following payment systems: debit card, mobile money, QR code, and NFC. Beneficiaries utilized the funds for cash withdrawals and food purchases at branchless banking agents. The results of the pilot served as evidence-based policy approach for the government to conduct noncash social assistance reform and to issue new regulation. The government decided to use debit card for disbursing non-cash social assistance programme, and the implementation was started in 2017. The evaluation results and implementation findings provide input for the next two action research cycles: branchless banking agents are a suitable approach to serve the poor and biometric authentication is required to simplify transactions. Branchless banking solution is considered successful in many developing countries for providing formal financial services to the poor. This solution has been introduced in Indonesia since 2009. As of September 2019, there were more than 1.1 million branchless banking agents spread across Indonesia with total customers ii exceeding 25 million. The second action research cycle examines the business model of branchless banking agents. In 2018, a survey involving 768 branchless banking agents was performed to analyze their satisfaction and business continuity. The results of the analysis were used to propose the business model viability. There are several problems in using a debit card with a PIN, including the debit card is lost or damaged, the beneficiaries forget their PIN, and the debit card along with the PIN is given to someone else. Biometric authentication was considered capable of addressing these challenges. The third action research cycle evaluates the trial of government assistance programme disbursement using biometric authentication. In 2019, a pilot project involving 5,066 participants was conducted to test the payment solution using face recognition and fingerprint. They could make payments at kiosk by using their face and fingerprint. Smartphones with biometric reader application are used for biometric data enrolment and payments. The mixed methods approach was used for data collection and analysis. Descriptive statistics, structural equation modeling (SEM), and paired t-test were used for quantitative analysis. Business model canvas (BMC) was used to develop business model viability. Qualitative analysis was applied to analyze interviews, to summarize observations, and to confirm the results of quantitative analysis. The results of this dissertation study contribute to various substances: responding to the results of previous studies, recommending improvements to government policies, and providing insights for future implementation. The payment system research compares four payment solutions and proves that an evidence-based policy approach is effective for policy reform. Research on branchless banking formulates the variables that affect business satisfaction from both financial and non-financial factors, then proposes a business model that fits the Indonesian context. The biometric authentication research compares face recognition and fingerprint solutions and recommends things to consider for future implementation plans. From the three research projects, we found that the internet network is a crucial factor in conducting digital transactions. The use of innovation in the development of financial services through the disbursement of non-cash government assistance to the poor provides several benefits: (1) assisting the government in ensuring the right beneficiaries, (2) reducing fraud, (3) simplifying the transaction process, and (4) escalating digital payment ecosystem. Furthermore, the implementation of the non-cash social assistance reform has succeeded in providing new savings accounts for the unbanked. This approach has proven to increase Indonesia’s financial inclusion index.